Kasibahagua Meets Sassuma Arnaa: Truancy, Resilience and Indigenous Curricula - Kristensen, Melina L (2021)
This non-empirical thesis employed standpoint theory to explore how culturally relevant curricula and curricular resources aim to foster resilience while diminishing truancy among First Nations, Métis, and Inuit youths. First Nations, Métis, and Inuit curricula and curricular resources were explored for their potentials for undoing the negative repercussions that may come from using Western curricula formulations and processes. Based on my analysis, I concluded that teacher education programs can better equip educators educating Indigenous youths by utilizing curricula and curricular resources, built upon the premises of Indigenous paradigms, training infused with culturally relevant knowledge, and increased community involvement. Addressing such factors may aid in birthing resilience and reducing truancy.